WOMEN’S INFLUENCING FACTORS IN CHOOSING THE IUD CONTRACEPTION METHOD - Irisanna Tambunan; Udin Sabarudin; Hadyana Sukandar (Journal of Maternity Care and Reproductive Health, 2020)
The use of long-term contraception especially the Intra-Uterine Device (IUD) in Indonesia is still relatively low, one of which is West Java. Factors that influence the use of IUDs are sociodemographic, sociopsychological, and knowledge about family planning, but information about these factors is still limited in West Java. The purpose of this study was to determine the effect of sociodemographic factors, sociopsychology, and the level of knowledge about the IUD in women at Lembang District, West Bandung Regency, which is part of West Java Province. This quantitative research applied a case-control approach. Samples were selected by the Multistage random sampling technique, it divided into cases and control groups totaling 108 respondents. Data collection used a questionnaire. Bivariate statistical analysis was the Chi-square test, multivariable analysis was the Multiple Logistic Regression analysis. The results showed a significant influence of these factors on the choice of the IUD method including Sociodemographic factors: education (value p = 0.013), employment (value p = 0.014); Sociopsychological factors: perception of the ideal number of children (value p = 0.037), husband and wife communication (value p <0.001); knowledge factors about the benefits of the IUD, side effects of the IUD (value p <0.001) and side effects of the IUD (value p = 0.033). Multivariable analysis results showed that the working status was the most influential factor in choosing the IUDs in Lembang District (OR = 2.99 (95% CI): 2.49 (1.14-7.89). It is expected that health workers reactivated the program to increase knowledge in the community so it would change the perspective of women in choosing the IUD contraception method.Keywords: Factors, IUDs, knowledge, sociodemography, sociopsychology.